Association of Patient-Physician Language Concordance and Glycemic Control for Limited-English Proficiency Latinos with Type 2 Diabetes - Parker, Melissa M. (JAMA Intern Med, 2017)
IMPORTANCE: Providing culturally competent care to the growing number of limited English proficiency (LEP) Latinos with diabetes in the United States is challenging. OBJECTIVE: Evaluate changes in risk factor control among LEP Latinos with diabetes who switched from language discordant (English-only) to language concordant (Spanish-speaking) primary care providers or vice versa. DESIGN: Pre-post, difference-in-differences study. SETTING: Kaiser Permanente Northern California (KPNC), an integrated healthcare delivery system with access to bilingual providers and/or professional interpreter services. PARTICIPANTS: Adult diabetes patients (n=1,605), self-identifying as Latino, whose preferred language was Spanish (LEP) and switched providers between 2007-2013. Spanish-speaking and English-only providers were identified by self-report or utilization data. EXPOSURE: Change in patient-provider language concordance after switching providers. OUTCOMES: Glycemic control (HbA1c < 8%), poor glycemic control (HbA1c > 9%), LDL control (LDL < 100 mg/dL), and systolic blood pressure control (sBP < 140 mmHg). RESULTS: There was a significant net improvement in glycemic and LDL control among LEP Latinos who switched from language discordant to concordant providers relative to those who switched from one discordant to another discordant provider. After adjustment and accounting for secular trends, the prevalence of glycemic control increased by 10% (95% CI: 2% to 17%; p=0.01), poor glycemic control decreased by 4% (95% CI: −10% to 2%; p=0.16) and LDL control increased by 9% (95% CI: 1% to 17%; p=0.03). No significant changes were observed in SBP control. Prevalence of LDL control increased 15% (95% CI: 7% to 24%; p=0.0004) among LEP Latinos who switched from concordant to discordant providers. Risk factor control did not worsen following a provider switch in any group. CONCLUSIONS AND RELEVANCE: We observed significant improvements in glycemic control among LEP Latino diabetes patients who switched from language discordant to concordant providers. Facilitating language concordant care may be a strategy for diabetes management among LEP Latinos.